The feasibility and safety of disposable endoscope vs. conventional endoscope for upper gastrointestinal tract examination: a multicenter, randomized, parallel, non-inferiority trial - Li, De-feng; Shi, Rui-yue; Tian, Yan-hui; Xu, Zheng-lei; Zhou, Ying-sheng; Sun, Xian-jiu; Cai, Jin-wei; Fang, Yuan-yuan; Peng, Huan; Wang, Jia-min; Dong, Tao; Cai, Yong-de; Yao, Jun; wang, Li-sheng (Zeitschrift für Gastroenterologie, 2021)
Background A disposable upper gastrointestinal endoscope can effectively decrease infectious outbreaks associated with endoscope reuse. In the present study, we aimed to evaluate the feasibility and safety of a disposable endoscope for upper gastrointestinal examination.Methods In a prospective, randomized trial, 144 upper endoscopic procedures were allocated to either the disposable endoscope group or the conventional endoscope group. The primary outcomes were rates of excellent and good image qualities and maneuverability satisfaction. The second outcome included procedure duration, endoscopic diagnosis, and adverse events.Results A total of 144 subjects were enrolled in the present analysis and prospectively randomized to 2 study groups. Finally, 70 and 69 subjects were enrolled in the novel disposable endoscope group and the conventional endoscope group, respectively, due to the schedule cancellation of 5 subjects. The baseline characteristics of the patients were similar in both groups. The excellent and good image quality rates and maneuverability satisfaction of the novel disposable endoscope were not inferior to the conventional endoscope (p = 0.99 and p = 0.99, respectively). Moreover, no significant between-group difference was observed in the endoscopic results and adverse events (p = 0.30 and p = 1, respectively). However, the procedure duration in the novel disposable endoscope was longer compared with the conventional endoscope (8.40 ± 4.28 min vs. 5.12 ± 2.65 min, p < 0.001).Conclusions The novel disposable endoscope was as safe, effective, and maneuverable as a conventional endoscope. However, the novel disposable endoscope was associated with a longer procedure duration.
Keywords: neuartiges Einweg-Endoskop; Durchführbarkeit; Sicherheit